Master's Degrees in Design Management: What's in a Name?. (September 2017) - Herbst, Walter; McDonagh, Deana
Abstract : You're a manager in a design‐centric company looking to hire someone proficient in product design, development, and management. You post the job—and get resumes from new designers with master's degrees in a dozen differently named programs. Do these people all have the same skills? Don't you wish you were just hiring an MBA? Everyone knows what that means.